A multicenter prospective study of the treatment and outcome of patients with gastroduodenal peptic ulcer bleeding in Japan. Issue 49 (9th December 2022) - Kawaguchi, Koichiro; Yoshida, Akira; Yuki, Takafumi; Shibagaki, Kotaro; Tanaka, Hisao; Fujishiro, Hirofumi; Miyaoka, Youichi; Yanagitani, Atsushi; Koda, Masaharu; Ikuta, Yukihiro; Hamamoto, Tetsuro; Mukoyama, Tomoyuki; et al.
Abstract : Gastroduodenal peptic ulcers are the main cause of nonvariceal upper gastrointestinal bleeding (UGIB). We believe that recent advances in endoscopic techniques and devices for diagnosing upper gastrointestinal tract tumors have advanced hemostasis for UGIB. However, few prospective multicenter studies have examined how these changes affect the prognosis. This prospective study included 246 patients with gastroduodenal peptic ulcers treated at 14 participating facilities. The primary endpoint was in-hospital mortality within 4 weeks, and the secondary endpoints required intervention and refractory bleeding. Subsequently, risk factors affecting these outcomes were examined using various clinical items. Furthermore, the usefulness of the risk stratification using the Glasgow-Blatchford score, rockall score and AIMS65 based on data from the day of the first urgent endoscopy were examined in 205 cases in which all items were complete there are two periods. Thirteen (5%) patients died within 4 weeks; and only 2 died from bleeding. Significant risk factors for poor outcomes were older age and severe comorbidities. Hemostasis was required in 177 (72%) cases, with 20 cases of refractory bleeding (2 due to unsuccessful endoscopic treatment and 18 due to rebleeding). Soft coagulation was the first choice for endoscopic hemostasis in 57% of the cases and was selected in more than 70% of the cases where combined use was required. Rockall score and AIMS65 predicted mortality equally, and Glasgow-Blatchford score was the most useful in predicting the requirement for intervention. All scores predicted refractory bleeding similarly. Although endoscopic hemostasis for UGIB due to peptic ulcer had a favorable outcome, old age and severe comorbidities were risk factors for poor prognosis. We recommend that patients with UGIB should undergo early risk stratification using a risk scoring system.